ANALISIS DAYA DUKUNG LAHAN TANAMAN SAGU DI KABUPATEN KONAWE - Agus Zakaria; La Rianda; R. Marsuki Iswandi; Budiyanto Budiyanto (Universitas Halu Oleo, 2017)
Sago is one of plants that produce carbohydrate and has important role for Indonesia daily diet after rice, corn, and cassavas. Konawe Regency is one of the potential to grow sago in Indonesia, with the largest area covered 40,06 percent from the total of the land of sago in the Province of Southeast Sulawesi 5.024 ha. The purposes of the study were to analyze the supporting power of the land of sago in Konawe Regency; analyze the ratio of employeent absorbtion; analyze the income of the farmers of sago processor. The study was conducted in Besulutu Sub-District Konawe Regency. The population was the farmers and the owner of sago involved intoo sago enterpreneurship. The technique of sample was determined by using purposive sampling method. The data was analyzed by using descriptive analysis. Results of the research shown that the supporting power of sago plantation based on actual income to fulfill the need of the farmers was about 9 person/hectare/year. In general, the absorbtion of the employement in sago entrepreneurship was about 4 HKP/cycle of the production with the averages number 892 HOK/hectare/year, while the optimalization of the employement total absorbed was 1.784 HOK/hectare/year. The income of the farmer from sago entrepreneurship in one cycle of the production was Rp 3.493.000,-Keywords